Uneven load contact dynamic modelling and transmission error analysis of a 2K-V reducer with eccentricity excitation - Wang, Guangjian (Strojniški vestnik, 2020)
In this paper, the formula of non-load transmission error (TE) and time-varying backlash is derived through the incremental meshing line method based on the eccentricity error model of 2K-V gear pair with small tooth difference. Considering the influence of uneven load contact between two gear pairs with small tooth difference, the static transmission error (STE) of a 2K-V gear pair with small tooth difference is deduced. This work helps to predict the TE caused by eccentricity error and provide inference to compensate backlash. Also, we establish the nonlinear dynamic model of 2K-V small tooth difference under eccentricity excitation, in which non-linear factors such as non-uniform load, time-varying backlash, transmission error and contact stiffness are considered, and validated the theoretical model by comparing the dynamic transmission error in simulation and in theory. Furthermore, the transmission error of the 2K-V gear reducer was tested, and the test results further verified the uneven load contact phenomenon of the gear pair with small tooth difference in the meshing process. At the same time, the experimental transmission error frequency spectrum is consistent with the theoretical results, indicating that the transmission accuracy of the 2K-V reducer is mainly caused by the eccentricity error of the gear pair with small tooth difference. Finally, we optimized the initial eccentricity phase and predicted the minimum transmission error, providing theoretical guidance for the assembly of 2K-V small tooth difference gear pairs.
Keywords: 2K-V reducer; časovno spremenljiv razstop; eccentricity error; napaka ekscentričnosti; napaka prenosa; neenakomerne kontaktne obremenitve; nelinearna dinamika; nonlinear dynamics; reduktor 2K-V; transmission error; uneven load contact